ANALISIS TREN PESERTA DANA PENSIUN DI INDONESIA - Susanawati, Dewi; Nuraini, Ani; Jalaludin, Paiz; Mufaridho, Lailatul Maziyah Wildan (POLITEKNIK LP3I JAKARTA, 2025)
Indonesia ranks 7th globally in terms of Purchasing Power Parity (PPP) and 17th in nominal GDP, recording 5.02% year-on-year growth in the fourth quarter of 2024. Despite this positive performance, pension fund participation has remained stagnant since the enactment of Law No. 11/1992. Data from the Financial Services Authority (OJK) show that pension benefit liabilities increased by 4.6% (YoY) to IDR 393.52 trillion, while participant contribution growth slowed to 1.92% (YoY). This study applies trend analysis using trend models within a time series framework to forecast the growth of pension fund participants. The exponential trend model was found to be the most accurate, with the lowest Standard Error of the Estimate. Projections indicate an increase in participants for the Financial Institution Pension Fund (DPLK) and a decline for the Employer Pension Fund (DPPK). These results provide insights for stakeholders to formulate strategies that enhance pension fund participation and ensure long-term benefit sustainability.